Pengaruh Pendekatan Keterampilan Proses Sains terhadap Hasil Belajar Siswa Kelas IV SS Masyithoh Ngoro - Sari, Mita Merinda; Shofiyah, Noly (Indonesian Journal Publisher, 2024)
Research has been carried out at the Masyithoh Ngoro elementary school on the effect of the Science Process Skills Approach on the learning outcomes of fourth grade students at the Masyithoh Ngoro elementary school. This thesis aims to determine the effect of the Science Process Skills Approach on student learning outcomes. This type of research includes a pre-experimental design with one group pretest and posttest design. The population in this study were all fourth-grade students at SD Masyithoh Ngoro. The results of this study indicate that the data on student learning outcomes after participating in learning with the Science Process Skills Approach is higher than the student learning outcomes before the Science Process Skills Approach is applied. This shows that there is an influence of the science process skills approach on learning outcomes. Evidenced by the results of the t test of 10,490 with a significance value of 5%. So, it can be concluded that there is an influence of the Science Process Skills Approach because t count is greater than t table, namely 10.490 > 2.045, then Ha is accepted and Ho is rejected. From these data it shows that there is an influence of the science process skills approach on learning outcomes.